A new strategy to maximize organic matter valorization in municipalities: Combination of urban wastewater with kitchen food waste and its treatment with AnMBR technology. (April 2017) - Moñino, P.; Aguado, D.; Barat, R.; Jiménez, E.; Giménez, J.B.; Seco, A.; Ferrer, J.
Abstract: The aim of this study was to evaluate the feasibility of treating the kitchen food waste (FW) jointly with urban wastewater (WW) in a wastewater treatment plant (WWTP) by anaerobic membrane technology (AnMBR). The experience was carried out in six different periods in an AnMBR pilot-plant for a total of 536 days, varying the SRT, HRT and the food waste penetration factor (PF) of food waste disposers. The results showed increased methane production of up to 190% at 70 days SRT, 24 h HRT and 80% PF, compared with WW treatment only. FW COD and biodegradability were higher than in WW, so that the incorporation of FW into the treatment increases the organic load and the methane production and reduces sludge production (0.142 vs 0.614 kg VSS kg removed COD −1, at 70 days SRT, 24 h HRT and 80% PF, as compared to WW treatment only).